PENERAPAN PEMBELAJARAN TIK (TEKNOLOGI INFORMASI DAN KOMUNIKASI) PADA EKSTRAKURIKULER KOMPUTER DI TAMAN KANAK-KANAK NEGERI 2 YOGYAKARTA - Ratih Septianna (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2023)
The development of technology has touched aspects of education, including early childhood. Learning using computer devices, which is usually introduced at elementary school level, can already be done in early childhood This research aims to describe the application of learning using Information Communication Technology (ICT) in the form of computer devices in early childhood. The subjects in this research were the school principal, computer extracurricular teacher and students at TK Negeri 2 Yogyakarta. The method used in this research is descriptive qualitative while data collection uses interviews, observation and documentation studies. Based on research, the results showed that ICT learning at TK Negeri 2 Yogyakarta was included in the extracurricular activity program using computer devices and application-based educational games . The extracurricular teacher coordinates with the class teacher to adjust the type of activity to the theme, learning objectives and level of difficulty according to the student's age group. The material provided includes an introduction to hardware, an introduction to geometric shapes, colors, an introduction to letter and number symbols through games. The methods used in computer learning are demonstration methods, direct practice and games. Through computer learning, it is easier for teachers to convey teaching material and students are more interested in the learning being carried out.